Hybrid adhesive joints - Silva, Lucas F. M.; Pirondi, Alessandro; Ochsner, Andreas (Advanced structured materials, 2011)
This volume presents material science and mechanical issues of hybrid adhesive bonds which are a combination of adhesive bonding and mechanical fastening, interference or welding. The hybrid concept includes also mixed-adhesive bonding, where at least two adhesives with different mechanical properties are placed along the bondline. The idea of hybrid joints is to gather the advantages of the different techniques leaving out their problems. Some of the advantages of these joints are a higher static and fatigue strength and a higher stiffness with respect to simple joints, a two-stage failure process and improved durability. The book treats all important kinds of hybrid joints which are in use today: weld - adhesive, rivet - adhesive, clinch - adhesive, bolt - adhesive, and adhesive - adhesive. A section dedicated to threadlocking and interference-fit adhesive joints is also included. All sections are treated from a scientific point of view with modeling issues supported by simple coupons testing and a technological point of view where the idea is to present more applied results with practical cases.